Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1161/hypertensionaha.107.088708
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognostic Value of Blood Pressure Variability in the General Population

Abstract: Abstract-The hypothesis has been advanced that cardiovascular prognosis is related not only to 24-hour mean blood pressure but also to blood pressure variability. Data, however, are inconsistent, and no long-term prognostic study is available. In 2012 individuals randomly selected from the population of Monza (Milan), 24-hour ambulatory blood pressure (Spacelabs 90207) was measured via readings spaced by 20 minutes. Systolic and diastolic blood pressure variability was obtained by calculating the following: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
3
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(163 citation statements)
references
References 31 publications
(27 reference statements)
3
145
3
12
Order By: Relevance
“…Thus, this study suggests that home blood pressure measurement may be a suitable alternative if a correct blood pressure target is chosen, but more studies are needed before home blood pressure can be recommended for antihypertensive treatment titration. Finally, it has to be emphasized that in contrast to home blood pressure measurement, 24-h blood pressure measurement can give additional important information about night-time blood pressure, 9 dipping status [26][27][28] or 24-h blood pressure variability, 13 all of which may lead to improved risk stratification of individuals with hypertension. On the other hand, potential drawbacks of 24-h blood pressure measurement include additional costs and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study suggests that home blood pressure measurement may be a suitable alternative if a correct blood pressure target is chosen, but more studies are needed before home blood pressure can be recommended for antihypertensive treatment titration. Finally, it has to be emphasized that in contrast to home blood pressure measurement, 24-h blood pressure measurement can give additional important information about night-time blood pressure, 9 dipping status [26][27][28] or 24-h blood pressure variability, 13 all of which may lead to improved risk stratification of individuals with hypertension. On the other hand, potential drawbacks of 24-h blood pressure measurement include additional costs and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…3 Accordingly, ambulatory blood pressure measurement is a better predictor of cardiovascular morbidity and mortality than office blood pressure. [8][9][10][11][12][13][14][15] Randomized studies using ambulatory blood pressure measurement for the management of antihypertensive treatment are scarce. 16 In one study, less intensive antihypertensive drug treatment was observed with the use of 24-h blood pressure measurement, whereas overall blood pressure con-trol was maintained in both treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…or CV of BP was used as an index of variability in HBP. 3,13,14 The Ohasama study reported that the s.d. of BP was significantly and positively correlated with the ambulatory BP, but the CV of SBP was independent of SBP.…”
Section: Coefficient Variation Of Home Blood Pressure E Ushigome Et Almentioning
confidence: 99%
“…Recent studies have explored the association between variability in BP and cardiovascular events, and they demonstrated that variability in BP predicted the risk of stroke and left ventricular hypertrophy. [3][4][5] To our knowledge, no reports have explained the relationship between variability in HBP and target organ damage in diabetic patients. Therefore, we investigated the relationship between variability in HBP and diabetic nephropathy in Japanese patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that short-term variability of blood pressure, with use of 24-h ambulatory monitoring or home blood pressure recordings, predicts cardiovascular risk. 11 Furthermore, long-term blood pressure variability, as represented by s.d. of long-term clinic blood pressure measurements or maximum blood pressure reached, has been shown to independently and even more strongly associated with cardiovascular risk compared with longterm averaged blood pressure.…”
mentioning
confidence: 99%